Factors influencing trunk control recovery after intensive rehabilitation in post-stroke patients: a multicentre prospective study. Issue 2 (17th February 2023) - Pellicciari, Leonardo; Sodero, Alessandro; Campagnini, Silvia; Guolo, Erika; Basagni, Benedetta; Castagnoli, Chiara; Hochleitner, Ines; Paperini, Anita; Gnetti, Benedetta; Avila, Lucia; Romano, Emanuela; Grippo, Antonello; et al.
ABSTRACT: Background: Trunk control plays a crucial role in the stroke rehabilitation, but it is unclear which factors could influence the trunk control after an intensive rehabilitation treatment. Objectives: To study which demographic, clinical and functional variables could predict the recovery of trunk control after intensive post-stroke inpatient rehabilitation. Methods: Subjects with acute, first-ever stroke were enrolled and clinical and data were collected at admission and discharge. The primary outcome was considered the trunk control measured by the Trunk Control Test (TCT). The data were analyzed by a univariate and multivariate logistic regressions. Results: Two hundred forty-one post-stroke patients were included. All baseline variables significantly associated to TCT at discharge in the univariate analysis (i.e. gender, NIHSS neglect item at admission, presence of several complexity markers, TCT total score at admission, NIHSS total score, pre-stroke modified Rankin Scale, Fugl-Meyer Assessment motor and sensitivity score) were entered in the multivariate analysis. The multivariate regression showed that age ( p = .003), admission NIHSS total score ( p = .001), admission TCT total score ( p < .001) and presence of depression ( p = .027) independently influenced the TCT total score at discharge ( R 2  = 61.2%). Conclusions: Age, admission neurological impairment (NIHSS total score), trunk control at the admission (TCT total score), and presence of depression independently influenced the TCT at discharge. These factors should be carefully assessed at the baseline to plan a tailoring rehabilitation treatment achieving the best trunk control performance at discharge.